O debate sobre facilitaç\~ao de investimentos - Renato Baumann Neves (Instituto de Pesquisa Econômica Aplicada (IPEA), 2020)
– This text presents the main points of the debate about the mechanisms of attraction and facilitation of foreign direct investment. Recently several countries have questioned the traditional model of investment agreements. One of the remarkable dimensions in the agenda of several multinational agencies is what type of conditions can be expected to form part of those agreements. One alternative is the model of agreement of cooperation and facilitation of investment adopted by Brazil.
Keywords: F21; F23; F55; F63; 330; foreign direct investment; economic growth; investment agreements